Physical and mechanical properties of titanium alloy VT1-0 after high-current electron beam irradiation - Klepikov, V.F.; Lonin, Yu.F.; Ponomarev, A.G.; Startsev, O.A.; Uvarov, V.T. (Вопросы атомной науки и техники, 2015)
Titanium alloy VT1-0 was modified by the high-current electron beam irradiation with energy 0.35 MeV, 5 μs impulse, and power density of 60 MW⋅cm-2. It was found that intense electron exposure significantly increased both hardness (by 30%) and elastic modulus (by 12%) within a subsurface layer of 100 μm thick. The thermoelastic model of the metal ablation was developed. Description of dynamics of the induced temperature and deformations distributions has been performed using the finite difference and finite element methods. Титановый сплав ВT1-0 модифицирован сильноточным электронным пучком с энергией 0,35 МэВ, импульсом 5 мкс и плотностью мощности 60 MВт⋅cm-2. Обнаружено, что облучение интенсивным электронным пучком существенно увеличивает твердость (на 30%) и модуль упругости (на 12%) приповерхностного слоя толщиной 100 мкм. Построенa термоэластическая модель абляции металла, согласно которой проведено описание динамики распределений температуры и деформаций методами конечных разностей и конечных элементов. Титановий сплав ВT1-0 модифіковано сильнострумовим електронним пучком з енергією 0,35 MeВ, імпульсом 5 мкс і густиною потужності 60 MВт⋅cm-2. Виявлено, що опромінення інтенсивним електронним пучком суттєво збільшує твердість (на 30%) та модуль пластичності (на 12%) приповерхневого шару товщиною 100 мкм. Розвинено термоеластичну модель абляції металу, згідно з якою здійснено опис динаміки розподілів температури та деформацій методами скінченних різниць та скінченних елементі